The Description of Smarthpone Addiction in Teenager 15-18 Years Old in Surabaya - Basiro, Alvina; Hakim Zakkiy Fassya , Abdul; Afridah, Wiwik (Rifa'Institute, 2023)
Introduction: The research was conducted by Aulia in 2019 observed that in their research sample 2.2% of teenagers showed a high risk of addiction and 9.3% moderate risk, while among teenagers, only 1% showed an increased risk of addiction and 6, 7% moderate risk. Objective: Therefore, this study aims to determine the description of smartphone addiction based on the components of smartphone usage, self-regulation, self-efficacy in teenagers aged 15-18 years in Surabaya city. Method: This research is a quantitative descriptive study with a cross-sectional approach. Result and Discussion: The results of this study indicate that addiction in teenagers aged 15-18 years which includes components of smartphone usage, self-regulation, and self-efficacy show that the results of smartphone usage in teenagers aged 15-18 years in Surabaya in a day 5-6 hours using a smartphone and 10-20 minutes they check their smartphone in a day. The results of the highest percentage of smartphone addiction obtained from the average respondents' answers on self-regulation indicators are 53.9% of teenagers do not experience addiction, because as many as 53.9% of teenagers have good self-regulation. Coclusion: The results of the highest percentage of smartphone addiction obtained from the average respondents' answers on self-efficacy indicators are 55.3% of teenagers do not experience addiction, because as many as 55.3% of teenagers have good self-efficacy